Heat stress affects floral morphology, silique set and seed quality in chamber and field grown winter canola. (20th March 2021) - Pokharel, Meghnath; Stamm, Michael; Hein, Nathan T.; Jagadish, Krishna S. V.
Abstract: The impact of heat stress coinciding with reproductive stages in winter canola was studied using walk‐in controlled environment chambers and field‐based tents. Six different cultivars (46W94, Edimax CL, Mercedes, Popular, DKW44‐10 and DKW46‐15) were used in both the experiments following a split‐plot design. Under controlled environment chambers, all six cultivars were exposed to HDT (day/night; 34/15°C), HNT (23/20°C), HDNT (34/20°C) and control (23/15°C) conditions for 14 days coinciding with flowering. Under field conditions, custom built 'heat tents' were used to impose heat stress starting seven days after 50% of flowering till maturity. The results demonstrated that HDT and HDNT induced significant impact on floral morphology, extreme levels of floral sterility and complete yield loss with two weeks of stress exposure during flowering. However, biomass, seed weight and oil concentration at maturity were either significantly increased or unchanged which demonstrated significant post‐stress phenotypic plasticity in canola to overcome damage caused by short episode of HDT and HDNT during flowering. The long duration heat stress under field conditions recorded significant decrease in yield parameters and oil concentration in the canola cultivars. Incorporating greater post‐stress phenotypic plasticity will help develop canola as an ideal alternative crop under future climates associated with enhanced frequency of short heat stress episodes coinciding with critical reproductive stages.